PEMBUATAN KRIM ANTI KETOMBE EKSTRAK ETANOL DAUN SIRSAK (Annona muricata L.) - Elfita, Elfita; Muharni, Muharni; Ferlinahayati, Ferlinahayati; Maryadi, Maryadi (Jurnal Pepadu, 2025)
Dandruff and hair loss are conditions that are often experienced by the community, especially mothers and young women. Various products are available on the market to overcome the problem of dandruff and hair loss, but at a relatively expensive. Many traditional medicinal plants are known to be effective as anti-dandruff. One of them is sirsak leaves (Annona muticata L.). For this reason, it is necessary to conduct socialization to the community, especially mothers and young women residents of RW 05 Indralaya Mulya, North Indralaya District, Ogan Ilir Regency, about the use of traditional medicinal plants to overcome dandruff and hair loss and introduce a simple formulation for making anti-dandruff hair cream. The results of the activity showed that the community was very familiar with the A. muricata plant, but did not know that A. muricata leaves could be used as an anti-dandruff ingredient. The community felt that they had gained practical knowledge about how to make anti-dandruff cream from traditional medicinal plants. This activity has increased the insight and knowledge of the community, especially residents of RW 05 Indralaya Mulya about the use of Sirsak leaves and making anti-dandruff cream.